Pengembangan Perangkat Pembelajaran Model PBL Berbantuan Simulasi PhET untuk Meningkatkan Kemampuan Berpikir Tingkat Tinggi - Arman Rizal Gunawan; Hikmawati Hikmawati; I Wayan Gunada; Susilawati Susilawati (Universitas Hamzanwadi, 2021)
This development research aims to produce a product in the form of a physics learning device with a problem based learning model on Momentum and Impulse material to improve students' higher-order thinking skills. The type of research is Research and Development (R&D) with a 4D model consisting of Define, Design, Develop, and Disseminate. The products developed are syllabus, online learning implementation plans, student worksheets equipped with PhET simulation instructions, and higher order thinking ability test instruments. Product validity was assessed by five validators with Likert scale analysis. Furthermore, the effectiveness of the device is determined from a limited trial to get the N-gain value. The results of the study based on the validator's assessment showed that the overall device developed had an average value of above 3.00 in the good category, then the average N-gain test results obtained a value of 0.34 in the medium category. Thus, it can be concluded that the development of problem based learning physics learning tools on Momentum and Impulse material is valid, and effective for improving students' higher order thinking skills.